2023
DOI: 10.1080/13510002.2023.2225675
|View full text |Cite
|
Sign up to set email alerts
|

Zinc improves sexual performance and erectile function by preventing penile oxidative injury and upregulating circulating testosterone in lead-exposed rats

Elizabeth Enohnyket Besong,
Tunmise Maryanne Akhigbe,
Precious Jesutofunmi Ashonibare
et al.

Abstract: Aim: The present study evaluated the effect of lead exposure with and without zinc therapy on male sexual and erectile function. Methods: Twenty male Wistar rats were randomly assigned into four groups; the control, zinc-treated, lead-exposed, lead + zinc-treated groups. Administrations were per os daily for 28 days. Results: Zinc co-administration significantly improved absolute and relative penile weights and the latencies and frequencies o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 74 publications
0
4
0
Order By: Relevance
“…These hormones stimulate the release of neurotransmitters, such as dopamine, which, in turn, increase locomotor activity and contribute to improved copulatory and sexual performance. During mating and sexual encounters, the circulation of testosterone in the body enhances sexual desire, motivation, and overall sexual function [30,31]. As illustrated in Table 3, the rats treated with sildenafil, ginseng, and MJ Cr.…”
Section: Resultsmentioning
confidence: 99%
“…These hormones stimulate the release of neurotransmitters, such as dopamine, which, in turn, increase locomotor activity and contribute to improved copulatory and sexual performance. During mating and sexual encounters, the circulation of testosterone in the body enhances sexual desire, motivation, and overall sexual function [30,31]. As illustrated in Table 3, the rats treated with sildenafil, ginseng, and MJ Cr.…”
Section: Resultsmentioning
confidence: 99%
“…Besong et al and Rafique et al reached similar conclusions regarding the positive effect of Zn on maintaining optimal testosterone levels. Additionally, Trumbo et al's study suggests that increasing dietary Zn intake within the recommended range may be beneficial in reducing the risk of erectile dysfunction [7,42,43]. An animal study conducted in 2009 demonstrated that rats receiving 5 milligrams per day of Zn supplementation exhibited improved sexual function, with similar positive effects observed in men, emphasizing the potential of Zn in arousal and erection maintenance [44].…”
Section: Discussionmentioning
confidence: 99%
“…A clinical study showed that changes in lipid levels can affect the secretion of reproductive hormones T, FSH, and LH, with T being the most serious [22]. Testosterone is an important hormone for the maintenance of male characteristics and has a very important role in spermatogenesis and development as well as in the maintenance of sexual function and is involved in a variety of physiological pathways in men [23][24][25]. Reduced testosterone levels can lead to disorders in spermatogenesis, which in turn reduces the total number of spermatozoa.…”
Section: Discussionmentioning
confidence: 99%